Strategi Optimalisasi Peranan Pendidikan Sekolah dalam Upaya Pencegahan Dini Tindak Pidana Korupsi - Loso .; Ahmad Suharto; Dwi Aryo Fajar (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
abstract Early  warning  of  corruption  crime  could  be  done  earlier  through  education.  School  could  make various  policy  strategy  in  building  anti-corruption  attitude  for  students.  This  research  aimed  to create  policy  strategy  for  building  anti-corruption  chacarcter  for  students.  This  research  used sociological juridic approach and descriptive analitic.From  the  research  result, school  could  do  several  steps  or  strategy  in  bilding  anti-corruption attitude through  :  1)  integrate  the anti-corruption  character  in  lessons  or  subject;  2)  uphold  the diciplines  of  the  school  rules  especially  when  examination  goes  on;  3) socialize  to  the  students about the crime of corruption; 4) build the canteen of honesty; 5) show the role model of honest and diciplines attitude to the students; 6) apply the transparent and accountability toward activities inn  the  school;  7)  integrate  to  the  extra  curicular  in  building anti-corruption  attitude;  8)  publish anti-corruption posters; 9) make anti-corruption education curriculumKeywords: corruption crime, policy strategy, Anti-corruption educatio